Organolentic Assessment Of Cenielia Asiatica By Taste Sensor. - Ismail, Zhari; Shafiqul Islam, A.K.M.; Ahmad, Mohd Noor; Othman, Prof.Madya Abdul Rahman; Mohd Shakaff, Ali Yeon (2005)
Medicinal plants and herbal preparations are usually evaluated utilizing methods such as physico-chemical, chemical, biological and pharmacognosical techniques. Organoleptic parameters such as taste, aroma and color are still useful to identify certain plants.